PETROLOGICAL, MINERALOGICAL AND GEOCHEMICAL DATA FROM THE EOHELLENIC OPHIOLITIC NAPPE IN THE ISLAND OF SKYROS, GREECE - Karkalis, C.; Magganas, A.; Koutsovitis, P. (Bulletin of the Geological Society of Greece, 2016)
The ophiolite of Skyros mainly consists of serpentinized harzburgites, gabbroic rocks, dolerites, tholeiitic basaltic lavas, rodingites, as well as ophicalcites. This ophiolitic sequence comprises of an ophiolitic mélange of pre-Upper Cretaceous age belonging to the Eohellenic nappe, has been affected by low to moderate metamorphic and metasomatic processes. Their mineral chemistry as well as their whole rock chemistry suggests that these ophiolitic rocks are associated with supra-subduction related processes. The presence of vesuvianite crystals in rodingites, as well as the occurrence of relict spinels within serpentinitic rocks, further confirms this assumption. Geochemical and petrological comparison between Skyros ophiolitic rocks and similar rocks of the Eohellenic nappe in East Thessaly and other N. Sporades islands, reveal that they all share many petrogenetical features. These eastcentral Greece Eohellenic ophiolites, and the ophiolitic rocks of the upper tectonic unit of the Attico-Cycladic Zone may possibly form an elongated ophiolitic zone associated to the hanging wall of the North Cycladic Detachment System